On the Interplay Between the Medicine of Hildegard of Bingen and Modern Medicine: The Role of Estrogen Receptor as an Example of Biodynamic Interface for Studying the Chronic Disease's Complexity - Melino, Sabrina; Mormone, Elisabetta (Frontiers in Neuroscience, 2022)
Introduction Hildegard of Bingen (1098-1179) interpreted the origins of chronic disease highlighting and anticipating, although only in a limited fashion, the importance that complex interactions among numerous genetic, internal milieu and external environmental factors have in determining the disease phenotype. Today, we recognize those factors, capable of mediating the transmission of messages between human body and environment and vice versa, as biodynamic interfaces. Aim We analyzed, in the light of modern scientific evidence, Hildegard of Bingen's medical approach and her original humoral theory in order to identify possible insights included in her medicine that could be referred to in the context of modern evidence-based medicine. In particular, the abbess's humoral theory suggests the identification of biodynamic interfaces with sex hormones and their receptors. Findings We found that the Hildegardian holistic vision of the organism-environment relationship can actually represent a visionary approach to modern endocrinology and that sex hormones, in particular estrogens, could represent an example of a biodynamic interface. Estrogen receptors are found in regions of the brain involved in emotional and cognitive regulation, controlling the molecular mechanism of brain function. Estrogen receptors are involved in the regulation of the hypothalamic-pituitary-adrenal axis and in the epigenetic regulation of responses to physiological, social, and hormonal stimuli. Furthermore, estrogen affects gene methylation on its own and related receptor promoters in discrete regions of the developing brain. This scenario was strikingly perceived by the abbess in the XIIth century, and depicted as a complex interplay among different humors and flegmata that she recognized to be sex specific and environmentally regulated. Viewpoint Considering the function played by hormones, analyzed through the last scientific evidence, and scientific literature on biodynamic interfaces, we could suggest Hildegardian insights and theories as the first attempt to describe the modern holistic, sex-based medicine. Conclusion Hildegard anticipated a concept of pathogenesis that sees a central role for endocrinology in sex-specific disease. Furthermore, estrogens and estrogen receptors could represent a good example of molecular interfaces capable of modulating the interaction between the organism internal milieu and the environmental factors.